Determining How Nurses Living With Their Families Decide to Work in a COVID-19 Intensive Care Unit: Grounded Theory Study - Akira Sato MSc; Yoshiko Sasaki PhD; Yoko Imazu PhD (SAGE Open Nursing)
Introduction Previous studies have shown that, during the coronavirus disease 2019 (COVID-19) pandemic, nurses were being reassigned to non-COVID-19 wards, opting to take leave, or resigning because of concerns of infecting their families. Even so, many nurses decided to continue working. However, a literature review revealed a lack of research clarifying how nurses coped with their anxiety and came to the decision to work in a COVID-19 intensive care unit. Objective To determine the process by which nurses living with their families decided to work in an intensive care unit during the COVID-19 pandemic and the factors that influenced their decision. Methods Fifteen registered nurses who lived with their families and decided to work in a COVID-19 intensive care unit during the pandemic were recruited for an individual, semi-structured interview. Charmaz's constructivist grounded theory was used to analyze the transcripts. Results Four core categories were identified. When the nurses perceived their facility would accept a patient with COVID-19, they: (1) assessed the risk of infection to their family, (2) weighed their anxiety against their sense of mission, (3) reduced the risk of infection, and (4) discussed the decision with their family members. Conclusion The decision involved fear of infecting families, trust in the hospital, and sense of mission. Hospitals’ consideration of the situation was important in motivating employees and reducing anxiety. There was a gender bias in this study. The large number of male participants resulted from the characteristics of the participating COVID-19 intensive care units, reflecting gender roles in Japan, where men often work and women are responsible for housework and childcare. Facilities and managers should foster a workplace culture that values employees, even in ordinary times. Our findings may help healthcare organizations support nurses in an emerging infectious disease pandemic and ensure nurses are available in healthcare systems with limited resources.